IMPLEMENTASI PERATURAN KEJAKSAAN REPUBLIK INDONESIA NOMOR 10 TAHUN 2019 TENTANG PERUBAHAN ATAS PERATURAN JAKSA AGUNG NOMOR PER-002/A/JA/05/2017 TENTANG PELELANGAN DAN PENJUALAN LANGSUNG BENDA SITAAN ATAU BARANG RAMPASAN NEGARA ATAU BARANG SITA EKSEKUSI DI KEJAKSAAN NEGERI KUANTAN SINGINGI - Nurjannah, Miftah; Artina, Dessy; Rauf, Muhammad A. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The Prosecutor’s execution auction come from found items and looted itemsrelated to evidence in criminal cases. The Prosecutor’s office is executor of courtdecisions that have been determined for evidence that has been decided to be returned,confifcated for destruction, confiscated for the state or auctioned.The type of research used is sociologicalresearch, using primary data obtaineddirectly at the research location throughdirect interviews with related parties andssecondary data obtained by means of library research in the form of books, scientificworks, related documents and internet sites related to the research this. The porposeof thisresearch is to determine the imp;ementation of the evidence auction at the KuantanSingingi District Prosecutor’s Office based on Prosecutor’s Regulation Number 10 of2019 and then obstacles to the implementation of the Prosecutor’s Office evidenceauction.Based on the research results, it is clear that the auction process for the executionof confiscated goods carried out by the Kuantan Singingi District Prosecutor’s Officeshows that there are still obstacle in its implementation. Coordination between variousgovernment agencies requires time because determining the limit price for goods to beauctioned cannotbe determined directly without a physical inspection of the goods. Thelow interest of auction participants also influences the implementation of the auctionbecause the large number of auction participants determines whether or not the items tobe auctioned will sell.Keywords: Prsecutor’s Office, Auction, Evidence.